Rosemary, the Beneficial Chemistry of a Garden Herb. (March 2016) - Hanson, James R.
The major natural products that are present in the garden herb, rosemary (Rosmarinus officinalis) including the mono di- and triterpenoid, flavonoid and phenolic constituents together with their biological activity as anti-microbial, anti-oxidant, anti-inflammatory, memory-enhancing and tumour-inhibitory agents, are reviewed.